Nonpharmacologic treatment of chronic insomnia - Morin, C; Hauri, P; Espie, C; Spielman, A; Buysse, D; Bootzin, R (1999)
This paper reviews the evidence regarding the efficacy of nonpharmacological treatments for primary chronic insomnia. It is based on a review of 48 clinical trials and two meta-analyses conducted by a task force appointed by the American Academy of Sleep Medicine to develop practice parameters on non-drug therapies for the clinical management of insomnia. The findings indicate that nonpharmacological therapies produce reliable and durable changes in several sleep parameters of chronic insomnia sufferers. The data indicate that between 70% and 80% of patients treated with nonpharmacological interventions benefit from treatment. For the typical patient with persistent primary insomnia, treatment is likely to reduce the main target symptoms of sleep onset latency and/or wake time after sleep onset below or near the 30-min criterion initially used to define insomnia severity. Sleep duration is also increased by a modest 30 minutes and sleep quality and patient's satisfaction with sleep patterns are significantly enhanced. Sleep improvements achieved with these behavioral interventions are sustained for at least 6 months after treatment completion. However, there is no clear evidence that improved sleep leads to meaningful changes in daytime well-being or performance. Three treatments meet the American Psychological Association (APA) criteria for empirically-supported psychological treatments for insomnia: Stimulus control, progressive muscle relaxation, and paradoxical intention; and three additional treatments meet APA criteria for probably efficacious treatments: Sleep restriction, biofeedback, and multifaceted cognitive-behavior therapy. Additional outcome research is needed to examine the effectiveness of treatment when it is implemented in clinical settings (primary care, family practice), by non-sleep specialists, and with insomnia patients presenting medical or psychiatric comorbidity.